Hotspot Stres Pada Guru Sekolah Dasar: Analisis Faktor-Faktor Pemicu dan Implikasinya Terhadap Kesejahteraan Pendidikan - Dawous, Gilang Gumilang; Satori, Djam’an; Munir, Munir; Suharto, Nugraha (Universitas Negeri Malang, 2024)
Abstract: Stress and burnout among elementary school teachers in Indonesia are critical issues impacting not only the well-being of educators but also the quality of education delivered to students. This study identifies multiple factors contributing to teacher stress, including high workloads, administrative demands, frequent curriculum changes, and socio-economic challenges. The impact of the COVID-19 pandemic further exacerbated these issues by introducing new challenges, such as the sudden transition to remote learning. Using a descriptive quantitative approach, data were collected from 175 elementary school teachers in Garut Regency through a semantic differential scale to measure stress levels. The findings revealed that the curriculum is the primary source of stress for teachers, followed by gender, age, school accreditation, employment status, and the presence of